Jessour for diversified and resilient agroecological systems to ensure food security and sustainable livelihoods in arid ecosystems - Louhaichi, Mounir; Gamoun, Mouldi (Université Laval, 2022)
Poster presented at the 5th World Congress on Agroforestry: “Transitioning to a Viable World”. Québec, Canada, July 17-20, 2022: For agricultural production, exploiting mountain slopes for rainwater runoff collection is a low-cost practice that supports sustainable agroecological systems and increases yield. To this day, people in rural communities continue to use an ancient and well-known system called Jessour to strengthen agricultural productive capacity and diversify their livelihoods. However, some effort is needed to maintain these systems and they require careful planning and engineering. A Jessour is composed of three parts, a sloping ground for collection, a terrace and an earth dyke. Jessour are mainly used for cultivating olive trees and sometimes dates, figs and almond trees. During rainy years, cereals (barley, wheat) and legumes (peas, lentils, broad beans) are cultivated between the trees. Once these crops are harvested, the crop residues are used as fodder for grazing livestock. Crop residues help fill feeding gaps, especially during the dry summer season. Livestock is continuously moved between trees, which allows rangelands to rest before winter dormancy. In arid areas of Southern Tunisia, Jessour are a vital agroecological system that support orchard plantation, annual crops and livestock, contribute to resilient, help sustain livelihoods for the majority of households and play an important role in ensuring food security under climate change and water scarcity. Therefore, greater attention is needed to establish and strengthen mechanisms that can make this proven technology more effective while conserving agrobiodiversity.